'They can't report abuse, they can't move out. They are at the mercy of these men': exploring connections between intimate partner violence, gender and HIV in South African clinical settings. Issue 5 (3rd May 2016) - Sprague, Courtenay; Hatcher, Abigail M.; Woollett, Nataly; Sommers, Theresa; Black, Vivian
Abstract: This qualitative study captured South African female health provider perspectives of intimate partner violence in female patients, gender norms and consequences for patients' health. Findings indicated female patients' health behaviours were predicated on sociocultural norms of submission to men's authority and economic dependence on their partners. Respondents described how men's preferences and health decision-making in clinics affected their patients' health. Adverse gender norms and gender inequalities affected women's opportunities to be healthy, contributing to HIV risk and undermining effective HIV management in this context. Some providers, seeking to deliver a standard of quality healthcare to their female patients, demonstrated a willingness to challenge patriarchal gender relations. Findings enhance understanding of how socially-sanctioned gender norms, intimate partner violence and HIV are synergistic, also reaffirming the need for integrated HIV-intimate partner violence responses in multi-sector national strategic plans. Health providers' intimate knowledge of the lived experiences of female patients with intimate partner violence and/or HIV deepens understanding of how adverse gender norms generate health risks for women in ways that may inform policy and clinical practice in South Africa and other high-HIV prevalence settings.